Combined 177Lu‐PSMA‐617 PRLT and abiraterone acetate versus 177Lu‐PSMA‐617 PRLT monotherapy in metastatic castration‐resistant prostate cancer: An observational study comparing the response and durability. Issue 15 (1st September 2021) - Suman, Sonam; Parghane, Rahul V.; Joshi, Amit; Prabhash, Kumar; Talole, Sanjay; Basu, Sandip
Abstract: Objective: The aim of present study was to determine and compare the overall response rates, progression‐free survival (PFS), overall survival (OS), and clinical toxicity of the combination of 177Lu‐PSMA‐617 radioligand therapy (PRLT) and abiraterone acetate (AA) versus 177Lu‐PSMA‐617 PRLT as monotherapy in metastatic castration‐resistant prostate cancer (mCRPC) patients. Materials and Methods: The mCRPC patients who received at least one cycle of 177 Lu‐PSMA‐617 PRLT with or without AA therapy, were included and analyzed in the present study. The patients were divided into two major groups. Group 1 received only 177 Lu‐PSMA PRLT and Group 2 received combined 177 Lu‐PSMA PRLT + AA therapy. Therapeutic dose of 177 Lu‐PSMA‐617 PRLT was 4.4–5.55 GBq per patient per cycle administered at intervals of 10–12 weeks in both groups. The Group 2 patients additionally received a dose of 1000 mg of AA once daily and 5 mg of prednisone twice daily. Treatment response in two groups was evaluated under four broad categories (a) symptomatic, (b) biochemical (serum prostate‐specific antigen level), (c) objective molecular imaging ( 68 Ga‐PSMA‐11 and 18 F‐FDG PET/CT), and (d) objective anatomical imaging (computed tomography). For assessing treatment response, patients in two groups were categorized into responders (complete response [CR], partial response [PR], and stable disease [SD]) and nonresponders (progressive disease [PD]). The Kaplan–Meier product‐limit method was used to calculate PFS and OS following first 177 Lu‐PSMA PRLT in the two groups. Univariate analysis was used to compare the patients' characteristics in two groups using a χ 2 or Fisher exact test. The Kaplan–Meier curves of PFS and OS between two groups were compared by using the log‐rank test ( p  < 0.05 significant). Results: A total of 58 mCRPC patients (Group 1, 38 patients and Group 2, 20 patients) were included in this study analysis. The clinical and demographic characteristics of these patients (age, Gleason score, FDG avid disease, metastatic disease burden, and average number of 177 Lu‐PSMA PRLT cycles) in two groups were compared and found to be similar ( p  > 0.05). Post‐treatment, symptomatic, biochemical, molecular, and anatomic imaging responders were found in 22 patients (58%) and 17 patients (85%), 22 patients (58%) and 16 patients (80%), 19 patients (54%) and 14 patients (78%), and 19 patients (54%) and 14 patients (78%) in Group 1 and Group 2, respectively. The median PFS of 7 months and median OS of 8 months were documented in Group 1, whereas median PFS was not reached and median OS of 16 months registered in Group 2. Transient hematological toxicity of Grades 1 and 2 was found in total seven patients (five patients in Group 1 and two patients in Group 2). On comparison of the treatment outcome between two groups, significant p value was found for symptomatic responders (58% in Group 1 vs. 85% in Group 2), median PFS (7 months in Group 1 vs. not reached in Group 2), and median OS (8 months in Group 1 vs. 16 months in Group 2), with better outcome in Group 2 patients for these variables. Conclusion: In the present study, the combination of 177 Lu‐PSMA‐617 PRLT and AA therapy showed significant improvement in mCRPC patients' symptomatic response, PFS, and OS as compared to 177 Lu‐PSMA‐617 PRLT monotherapy.